2018
DOI: 10.1021/acs.analchem.7b04608
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Isoelectric Focusing-Mass Spectrometry Method for the Separation and Online Characterization of Intact Monoclonal Antibody Charge Variants

Abstract: We report a new online capillary isoelectric focusing-mass spectrometry (CIEF-MS) method for monoclonal antibody (mAb) charge variant analysis using an electrokinetically pumped sheath-flow nanospray ion source and a time-of-flight MS with pressure-assisted chemical mobilization. To develop a successful, reliable CIEF-MS method for mAb, we have selected and optimized many critical, interrelating reagents and parameters that include (1) MS-friendly anolyte and catholyte; (2) a glycerol enhanced sample mixture t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 49 publications
(92 reference statements)
4
82
0
Order By: Relevance
“…Dai et al. reported a CIEF‐MS application for the separation and characterization of mAb charge variants as can be seen in Fig. .…”
Section: Analytical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al. reported a CIEF‐MS application for the separation and characterization of mAb charge variants as can be seen in Fig. .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Due to a larger injection volume applicable to the iCIEF system, low-abundance basic variants of stressed trastuzumab could be characterized. Dai et al reported a CIEF-MS application for the separation and characterization of mAb charge variants [73] as can be seen in Fig. 4.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…A sandwich configuration containing the catholyte segment, the sample segment containing analyte and carrier ampholytes, and the anolyte segment in the IEF capillary was used to avoid the exchange step and achieve full automation . Direct online cIEF–MS analysis of intact mAbs have been reported using either a stainless‐steel flow‐through microvial interface , or a pulled‐glass electrokinetically pumped sheath‐flow interface . The reported total ion chromatograms (TIC) containing structural information demonstrated high similarity to imaging IEF traces of identical mAbs .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the cIEF column with immobilized CAs could be carried out with high detection sensitivity even at low wavelengths. At the same time, coupling cIEF with MS could be also easier to implement, which would provide an important information on both isoelectric points (pIs) and molecular weights of target proteins, and then would greatly facilitates the profiling of proteome and the discovery of biomarker .…”
Section: Introductionmentioning
confidence: 99%